Clinical and radiological course of asymptomatic and hemodynamically stable moyamoya disease: a systematic review and meta-analysis - Yang Chen; Yang Chen; Yang Chen; Yang Chen; Zixuan Zhou; Zixuan Zhou; Zixuan Zhou; Zixuan Zhou; Bingyang Qin; Bingyang Qin; Bingyang Qin; Bingyang Qin; et al. (Frontiers in Neurology, 2025)
BackgroundMoyamoya disease (MMD) is an idiopathic, chronic intracranial vascular stenosis and occlusion disease. However, there is currently a lack of comprehensive analysis on the clinical and radiological course of asymptomatic MMD (AMMD) and hemodynamically stable MMD (HSMMD).Data sourceWe conducted a comprehensive literature search using major bibliographic indexing databases, including Embase, Medline, PubMed, Web of Science, and Cochrane Library.MethodsThis systematic review was conducted based on the PRISMA guidelines. The quality of the included studies was accessed using the Methodological Index for Non-Randomized Studies (MINORS). Effect sizes were pooled with a random-effects model. Heterogeneity between studies was estimated via the I2 test. Publication bias was assessed with Egger’s test. The registration code is CRD42023444432.ResultA total of seven AMMD studies were included in a meta-analysis, involving 393 patients and 649 hemispheres. Three HSMMD studies were all from the same institution. The pooled rate for clinical progression, hemorrhagic stroke, ischemic stroke, transient ischemic attack (TIA), and radiological progress of conservative group was 10% (95% CI 4.9–15.1%), 3.8% (95% CI 0.4–7.2%), 0.7% (95% CI 0–2.3%), 3.6% (95% CI 0.6–6.6%), and 15.6% (95% CI 10.2–22.1%), respectively. The pooled rate for stroke, TIA, and radiological progress of the surgical group was 3.7% (95% CI 0–10.8%), 0.2% (95% CI 0–3.0%), and 4.8% (95% CI 0–10.5%), respectively. Revascularization did not show a protective effect on TIA and radiological progression for AMMD.ConclusionAMMD and HSMMD present a concerning risk of clinical and radiological progression over a follow-up period of more than 2 years. Further high-quality studies are needed to optimize treatment strategies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=444432, CRD42023444432.